Cochrane Database of Systematic Reviews 2006
DOI: 10.1002/14651858.cd004272.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Surgery versus primary endocrine therapy for operable primary breast cancer in elderly women (70 years plus)

Abstract: Primary endocrine therapy should only be offered to women with oestrogen receptor (ER) positive tumours who are unfit for or who refuse surgery. In a cohort of women with significant co-morbid disease and ER-positive tumours it is possible that primary endocrine therapy may be a superior option to surgery. Trials are needed to evaluate the clinical effectiveness of aromatase inhibitors as primary therapy for an infirm older population with ER-positive tumours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(68 citation statements)
references
References 39 publications
4
63
0
1
Order By: Relevance
“…Full details of the methods employed are published elsewhere (Hind et al, 2006). The Cochrane Breast Cancer Group Specialised Register was searched on 29 June 2005.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Full details of the methods employed are published elsewhere (Hind et al, 2006). The Cochrane Breast Cancer Group Specialised Register was searched on 29 June 2005.…”
Section: Methodsmentioning
confidence: 99%
“…In some cases, the internal validity of the primary studies was affected by competing risks and informative censoring, which violate the assumptions underlying the Kaplan -Meier survival analysis method (these issues are discussed fully elsewhere in Hind et al, 2006). Heterogeneity between trials, in terms of interventions and outcome assessment, also made assessment of some outcomes problematic.…”
Section: Strengths and Weaknesses Of The Studymentioning
confidence: 99%
“…A series of randomised trials compared tamoxifen alone versus surgery alone [15][16][17] and a recent meta-analysis comparing surgery with primary endocrine therapy for operable breast cancer in elderly women found no difference in overall survival [18]. Several randomised trials compared tamoxifen alone with surgery followed by tamoxifen and in all but one of these trials there was a significant increase in local events in the tamoxifen alone group [19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…One study also showed a significantly higher mortality in patients treated by tamoxifen alone but this increase in mortality was only apparent after 3 years of follow up [11]. A meta-analysis found a non-significant trend in favour of combining surgery with tamoxifen versus tamoxifen alone for overall survival (HR 0.86, P = 0.06) and a significant improvement in local disease control in favour of surgery and tamoxifen (HR 0.28, P \ 0.00001) [18]. Many of these early studies did not select patients based on oestrogen receptor status and all used tamoxifen.…”
Section: Discussionmentioning
confidence: 99%
“…PET is effective in around 80% of hormone receptor positive breast cancers [48]; there is, though, at present no way of predicting which receptor positive cancers will respond to endocrine therapy and how long the response will last [49]. The median response duration is about two years with wide variation [50].…”
Section: Primary Endocrine Therapy Vs Surgery Plus Endocrine Therapymentioning
confidence: 99%